Heterogeneous Workers, Trade, and Migration - Inga Heiland; Wilhelm Kohler (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop a model that combines monopolistic competition on goods markets with skill-type heterogeneity on the labor market to analyze the effects of trade and migration on welfare and inequality. Skill-type heterogeneity and partial specificity to firms' endogenously chosen skill requirements lead to endogenous worker-firm match quality, endogenous wage markups, and within-firm wage inequality. We identify novel effects of trade and migration. Trade enhances firms' monopsony power on the labor market and worsens the average quality of worker-firm matches, but the gains from trade theorem survives. Integration of labor markets leads to two-way migration between symmetric countries. Migration enhances competitiveness on the labor market and tends to increase the average quality of worker-firm matches. Trade and migration are complements. Our model clearly advocates opening up labor markets simultaneously with trade liberalization.
Keywords: F12; F16; F22; J24; 330; two-way migration; gains from trade; heterogeneous workers